Adoption of Park’s Transformation for Inverter Fed Drive - Jayarama Pradeep; R. Devanathan (Institute of Advanced Engineering and Science, 2015)
Park’s transformation in the context of ac machine is applied to obtain quadrature voltages for the 3-phase balanced voltages. In the case of a inverter fed drive, one can adopt Park’s transformation to directly derive the quadrature voltages in terms simplified functions of switching parameters. This is the main result of the paper which can be applied to model based and predictive control of electrical machines. Simulation results are used to compare the new dq voltage modelling response to conventional direct –quadrature (dq) axes modelling response in direct torque control – space vector modulation scheme. The proposed model is compact, decreases the computation complexity and time. The model is useful especially in model based control implemented in real time, in terms of a simplified set of switching parameters.